A novel strategy to reduce trace element supplementation in the semi-solid anaerobic digestion with gradient ammonia concentration: the role of biochar. (15th April 2023) - Cai, Yafan; Meng, Xingyao; Hu, Kai; Zhao, Xiaoling; Usman, Muhammad; Esposito, Giovanni; Shen, Xia; Chen, Shanshuai
Graphical abstract: Highlight: Semi-solid anaerobic digestion of chicken manure was focused. Biochar could reduce 50% of optimal TEs in semi-solid anaerobic digestion. Biochar increased the proportion of TE' exchangeable fraction. Biochar reduced the formation of precipitation between TEs and H2 S. Abstract: Solid anaerobic digestion of chicken manure is prone to the accumulation of volatile fatty acids (VFAs). Addition of trace elements (TEs) is an effective way to stabilize the digestion system. However, excessive supplementation of TEs may eventually cause environmental pollution. Therefore, it is necessary to develop an environmentally friendly method to reduce the addition for TEs. In this study, we explored the possibility of reducing the supplement for TEs with the assistance of biochar. The results showed that addition of biochar resulted in a 50 % decrease in the need for TE supplementation when the organic loading rate (OLR) was 5 g TS −1 d −1 . Biochar increased the relative (+0.67–8.5 folds) and absolute amounts (0.1–104.6 mg kg −1 total solid (TS)) of the highly-bioavailable fraction of TEs (exchangeable fraction (F2)) by chemical adsorption. The conductivity of biochar increased from 4.2 to 38.4 mS m −1 after adsorbing TEs, which might explain the enrichment of conductive microorganisms (+16 folds) in the digestion system, such as Geobacter (34-fold increase). Substitution of TEs with biochar increased the absolute amounts of Methanosaeta, Mathanosarcina, Methanoculleus, and Methanospirillum by 72.7 %, 5.7 %, 46.1 % and 2.7 %, respectively, and propionate and butyrate oxidizing bacteria ( Syntrophomonas, Syntrophobacter, and Smithella ) had the highest abundance. In summary, beneficial interactions between biochar and TEs makes biochar an ideal material for reducing the amounts of TEs needed to stabilize the semi-solid anaerobic digestion (SSAD) system.